Radiation Effect on MHD Stagnation-Point Flow of a Nanofluid over an Exponentially Stretching Sheet - Mohd Zuki, Salleh; Imran, Anwar; Sharidan, Shafie (Institute of Research and Development of Walailak University, 2014)
This paper theoretically investigates the radiation effect on magnetohydrodynamics (MHD) stagnation-point flow of a nanofluid over an exponentially stretching sheet under the assumptions of a small magnetic Reynolds number. The sheet is stretched with an exponential velocity in the presence of a non-uniform magnetic field B applied in a transverse direction normal to the flow. By using the modified Bernoulli's equation, a highly nonlinear nanofluid problem is modeled for an electrically conducting nanofluid. The momentum, thermal and concentration boundary layer thicknesses are intensified for the incorporated flow parameters such as Brownian motion parameter Nb, thermophoresis parameter Nt, Prandtl number Pr, Lewis number Le, Hartmann number M and velocity ratio parameter ε. Also by an appropriate similarity transformation, the system of nonlinear partial differential equations is reduced to ordinary differential equations. These equations subjected to the boundary conditions are solved numerically using the Keller-box method. Numerical results are plotted and discussed for pertinent flow parameters. A comparison with existing results in the literature is also provided.